Method for producing nanoparticles containing low molecular weight amphiphilic block copolymers
The method of producing nanoparticles using low molecular weight amphiphilic block copolymers with reduced alcohol content and aqueous medium addition addresses the challenges of stability and redissolution time, achieving high-yield and stable nanoparticle production.
Patent Information
- Application Number
- JP2022540792
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-31
- Filing Date
- 2020-12-30
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2040-12-30
AI Technical Summary
Current methods for producing nanoparticles using low molecular weight amphiphilic block copolymers face challenges in achieving high yields with excellent stability while reducing redissolution time.
A method involving the use of low molecular weight amphiphilic block copolymers with a number average molecular weight of less than 3,800, where the alcohol content is reduced to less than 2.5 w/v% and an aqueous medium is added to form micelles, enhancing stability and reducing redissolution time.
This method significantly reduces precipitation of encapsulated drugs during nanoparticle production, improving stability and allowing for high-yield production of nanoparticles with a shorter redissolution time.
Smart Images

Figure 0007654671000001 
Figure 0007654671000002 
Figure 0007654671000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing nanoparticles containing a low molecular weight amphiphilic block copolymer, and more specifically, to a method for producing drug-containing nanoparticles using an amphiphilic block copolymer having a low molecular weight, thereby producing nanoparticles with excellent stability in a high yield. [Background technology]
[0002] In order to achieve the desired therapeutic effect of a bioactive agent, the drug administered in an appropriate amount must be delivered to target cells in the body. For this reason, submicron particulate drug delivery systems using biodegradable polymers have been studied, and representatively, nanoparticle systems and polymeric micelle systems using biodegradable polymers have been reported as techniques for changing the distribution of intravenously administered drugs in the body to reduce side effects and improve efficacy. Such drug delivery systems have been reported to control the release of drugs to target organs, tissues or cells, have excellent biocompatibility, and improve the solubilization ability of poorly soluble drugs and the bioavailability of drugs.
[0003] Currently, the polymers mainly used for the production of polymeric nanoparticles and polymeric micelles are double-block amphiphilic block copolymers (mPEG-PLA) consisting of a hydrophilic block such as monomethoxypolyethylene glycol (mPEG) and a hydrophobic block such as polylactic acid (PLA). This polymer is hydrolyzed in aqueous solution, so it is provided as a lyophilized powder or solid as a final product. In order to use the polymer as a drug carrier, it must be lyophilized and stored in a solid state, and then redissolved in distilled water immediately before use. Such polymers have the disadvantage that it takes a long time to redissolve as the molecular weight increases.
[0004] On the other hand, decreasing the molecular weight and shortening the redissolution time can result in significantly lower product quality, such as the formation of precipitates during the manufacturing process, reduced stability of the nanoparticles leading to precipitation during storage or transportation, or difficulties in achieving sufficient bioavailability when administered to patients.
[0005] Therefore, there is a need to develop nanoparticle drugs containing low molecular weight polymers that can reduce the redissolution time without affecting the stability of the nanoparticles. Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a method for producing drug-containing nanoparticles that can be redissolved in a short time with high yield and while maintaining stability, and to provide such nanoparticles. [Means for solving the problem]
[0007] In order to solve the above problems, the present invention provides The present invention provides a method for producing nanoparticles, comprising: (1) a step of mixing an active ingredient, an amphiphilic block copolymer having a number average molecular weight of less than 3,800, and a C1-C5 alcohol; (2) a step of removing the C1-C5 alcohol from the mixture obtained in step (1) to reduce the C1-C5 alcohol content in the mixture to less than 2.5 w / v %; and (3) a step of adding an aqueous medium to the mixture obtained in step (2) to form micelles.
[0008] In one embodiment, the removal of the C1-C5 alcohol may be carried out at a temperature above 30° C., more specifically, at a temperature above 30° C. and below 50° C. for less than 2 hours.
[0009] In one embodiment, the formation of the micelles may be carried out at a temperature below 35°C, more specifically at a temperature above 10°C and below 35°C.
[0010] In one embodiment, the step of forming micelles can include filtering the formed micelles.
[0011] In one embodiment, the method may further comprise the step of freeze-drying the micelles formed in step (3).
[0012] In one embodiment, the formed micelles may be kept at 0° C. to 15° C. before being lyophilized.
[0013] In one embodiment, the formed micelles can be lyophilized within 3 hours.
[0014] In one embodiment, the amphiphilic block copolymer can comprise a hydrophilic block (A) selected from the group consisting of polyethylene glycol or a derivative thereof, polyvinylpyrrolidone, polyvinyl alcohol, polyacrylamide, and combinations thereof; and a hydrophobic block (B) selected from the group consisting of polylactide, polyglycolide, poly(lactic acid-glycolide), polymandelic acid, polycaprolactone, polydioxane-2-one, polyamino acids, polyorthoesters, polyanhydrides, polycarbonates, and combinations thereof.
[0015] In one embodiment, the active ingredient may be a poorly water-soluble drug.
[0016] In another aspect of the present invention, there is provided a nanoparticle comprising an active ingredient, an amphiphilic block copolymer having a number average molecular weight of less than 3,800, and a C1-C5 alcohol, the C1-C5 alcohol content being less than 0-2.5 w / v %.
[0017] In one embodiment, the nanoparticles may be produced by the production method according to an embodiment of the present invention. Effect of the Invention
[0018] According to the present invention, precipitation of encapsulated drugs during the nanoparticle manufacturing process is significantly reduced, making it possible to produce drug-containing nanoparticles with improved stability and significantly reduced redissolution times in high yields. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The present invention will be described in detail below. In the present invention, the term "nanoparticle" can be used interchangeably with micelle or micelle composition. In one embodiment, a "nanoparticle" can have a submicron size (e.g., particle size), i.e., less than 1 micrometer (e.g., 10-900 nm, or 10-500 nm).
[0020] The term "amphiphilic block copolymer" can form micelles in aqueous solution and can be used interchangeably with "micellar polymer." The amphiphilic block copolymer may be an AB type double block copolymer or a BAB type triple block copolymer consisting of a hydrophilic block (A) and a hydrophobic block (B).
[0021] In one embodiment, the content of the hydrophilic block in the amphiphilic block copolymer may be 20 to 95% by weight, more specifically 40 to 95% by weight, based on 100% by weight of the total copolymer, and the content of the hydrophobic block in the amphiphilic block copolymer may be 5 to 80% by weight, more specifically 5 to 60% by weight, based on 100% by weight of the total copolymer.
[0022] In the present invention, the number average molecular weight of the amphiphilic block copolymer is less than 3800. When the number average molecular weight of the amphiphilic block copolymer is 3800 or more, the redissolution time may become long.
[0023] In one embodiment, the number average molecular weight of the amphiphilic block copolymer may be 1,500 or more, 2,000 or more, 2,500 or more, 3,000 or more, or 3,300 or more, and may be 3,700 or less, 3,600 or less, 3,580 or less, 3,550 or less, 3,500 or less, 3,450 or less, or 3,400 or less.
[0024] The hydrophilic block is a biocompatible polymer, and specifically may contain one or more selected from the group consisting of polyethylene glycol or a derivative thereof, polyvinylpyrrolidone, polyvinyl alcohol, polyacrylamide, and combinations thereof, and more specifically may contain one or more selected from the group consisting of polyethylene glycol, monomethoxypolyethylene glycol, and combinations thereof.
[0025] The hydrophobic block is a biodegradable polymer and may be a polymer of an alpha (α)-hydroxy acid-derived monomer, specifically, it may include one or more selected from the group consisting of polylactide, polyglycolide, poly(lactic acid-glycolide), polymandelic acid, polycaprolactone, polydioxane-2-one, polyamino acids, polyorthoesters, polyanhydrides, polycarbonates, and combinations thereof, and more specifically, it may include one or more selected from the group consisting of polylactide, polyglycolide, poly(lactic acid-glycolide), and combinations thereof.
[0026] In one embodiment, the C1-C5 alcohol may be methanol, ethanol, isopropanol, or a mixture thereof. The alcohol may be dissolved in water or may be mixed with an organic solvent such as acetone, tetrahydrofuran, acetic acid, acetonitrile, dioxane, or a combination thereof.
[0027] In one embodiment, the mixing of the active ingredient, the amphiphilic block copolymer, and the alcohol in the step (1) can be carried out at a temperature of 40° C. to 70° C. for 1 hour to 6 hours.
[0028] In one embodiment, the removal of the C1 to C5 alcohol in the step (2) can be carried out at a temperature of more than 30° C., more specifically, at a temperature of more than 30° C. and less than 50° C., for less than 2 hours.
[0029] More specifically, the alcohol removal can be carried out for 30 to 100 minutes, 40 to 80 minutes, or 50 to 70 minutes at a temperature higher than 30° C. and equal to or lower than 45° C., or 32 to 42° C. If the alcohol removal temperature is too high, related substances increase, and if it is too low, sufficient alcohol removal may be difficult.
[0030] The C1-C5 alcohol content in the mixture obtained after the alcohol removal (i.e., the mixture before micellization) is less than 2.5 w / v% (i.e., less than 0 to 2.5 w / v%), and more specifically may be 2.0 w / v% or less, 1.5 w / v% or less, 1.0 w / v% or less, 0.8 w / v% or less, 0.6 w / v% or less, or 0.5 w / v% or less. If 2.5 w / v% or more of alcohol remains in the mixture before micellization, precipitation of the drug or polymer may occur.
[0031] The aqueous medium used in the step of forming the micelles may be, for example, one selected from the group consisting of ordinary water, distilled water, distilled water for injection, physiological saline, 5% glucose, a buffer, and combinations thereof, but is not limited thereto.
[0032] In one embodiment, the formation of the micelles can be carried out at a temperature below 35°C, more specifically, at a temperature above 10°C and below 35°C.
[0033] More specifically, the micelles can be formed at 15°C to 32°C, 20°C to 30°C, or 25°C to 28°C. If the temperature during micelle formation is too high, there is a possibility that related substances will increase or the drug will precipitate, and if the temperature is too low, the mixture of polymer and drug will not dissolve sufficiently, and micelles will not be formed well or the micelle formation may take too long. The micellization can be performed for less than 5 hours, 30 minutes to 4 hours, 60 minutes to 4 hours, or 90 minutes to 3 hours and 30 minutes.
[0034] In one embodiment, the step of forming micelles can include filtering the formed micelles.
[0035] In one embodiment, the filtration can be performed using a 0.1 to 0.8 μm, 0.1 to 0.6 μm, or 0.2 to 0.5 μm filter at 0° C. to 25° C., 0° C. to 20° C., or 0° C. to 15° C. The filtration can be performed successively using different filters under different temperature conditions, or can be repeated several times depending on each step.
[0036] In one embodiment, when the formed micelles (or the formed and filtered micelles) are freeze-dried, the formed micelles can be kept at 0° C. to 15° C. before freeze-drying and can be freeze-dried within 3 hours. More specifically, the formed micelles can be kept at 0° C. to 12° C. or 0° C. to 10° C. before freeze-drying and can be applied to the freeze-drying step for 10 minutes to 3 hours, 30 minutes to 3 hours, or 1 hour to 3 hours.
[0037] In another embodiment, the formed micelles can be immediately applied to the lyophilization step without storage. "Maintaining" can be used interchangeably with storage.
[0038] In one embodiment, the freeze-drying is carried out in the presence of a freeze-drying aid (also called a lyophilizing agent). The freeze-drying aid can be selected from the group consisting of sugars, sugar alcohols, and mixtures thereof. The sugar can be one or more selected from the group consisting of lactose, maltose, sucrose, and trehalose, and the sugar alcohol can be one or more selected from the group consisting of mannitol, sorbitol, maltitol, xylitol, and lactitol. The freeze-drying aid is added so that the freeze-dried composition can maintain a solid state. In addition, the freeze-drying aid dissolves uniformly in a short time during the redissolution process after freeze-drying the polymeric nanoparticle composition. In one embodiment, the content of the freeze-drying aid is 1 to 90% by weight, more specifically 10 to 60% by weight, based on 100% of the total dry weight of the freeze-dried composition.
[0039] In one embodiment, the active ingredient may be a poorly water-soluble drug.
[0040] In one embodiment, the poorly water-soluble drug can be selected from drugs having a solubility in water (25° C.) of 100 mg / mL or less. The poorly water-soluble drug can be selected from, but is not limited to, anticancer agents, antifungal agents, immunosuppressants, analgesics, anti-inflammatory agents, antiviral agents, anxiolytic sedatives, contrasting agents, corticosteroids, diagnostic agents, diagnostic imaging agents, diuretics, prostaglandins, radiopharmaceuticals, sex hormones including steroids, and combinations thereof.
[0041] In one embodiment, the poorly water-soluble drug can be selected from anticancer drugs, specifically, it can be a taxane anticancer drug. The taxane anticancer drug can be, for example, one or more selected from the group consisting of paclitaxel, docetaxel, 7-epipaclitaxel, t-acetylpaclitaxel, 10-desacetylpaclitaxel, 10-desacetyl-7-epipaclitaxel, 7-xylosylpaclitaxel, 10-desacetyl-7-glutarylpaclitaxel, 7-N,N-dimethylglycylpaclitaxel, 7-L-alanylpaclitaxel and cabazitaxel, more specifically, it can be paclitaxel, docetaxel or a combination thereof.
[0042] According to another aspect of the present invention, there is provided a nanoparticle comprising an active ingredient, an amphiphilic block copolymer having a number average molecular weight of less than 3,800, and a C1-C5 alcohol, the C1-C5 alcohol content being less than 0-2.5 w / v %.
[0043] The nanoparticles may be prepared by a method according to an embodiment of the present invention.
[0044] In one embodiment, the nanoparticles may be freeze-dried and have a re-dissolution time in an aqueous solution of 5 minutes or less, 4 minutes or less, or 3 minutes or less. The re-dissolution time can be measured by a conventionally known method, and can be measured as the time required to stir the freeze-dried nanoparticles in an aqueous solution at 400 to 600 rpm at room temperature until the solution becomes transparent.
[0045] The nanoparticles according to one embodiment may have a drug precipitation time of 6 hours or more, 8 hours or more, 10 hours or more, or 12 hours or more after preparation as a solution. The precipitation time can be measured by a conventional method, for example, by dissolving the nanoparticles in an aqueous solution to produce a clear solution, and then allowing the solution to stand at room temperature, and measuring the time it takes for the solution to become cloudy or for precipitation to be observed.
[0046] In order to facilitate understanding of the present invention, examples are provided below. However, the following examples are only for understanding the present invention, and the scope of the present invention is not limited thereby in any way. EXAMPLES
[0047] Examples 1 to 3 and Comparative Example 1: Preparation of polymeric micelles containing docetaxel depending on the ethanol removal temperature 19 g of monomethoxypolyethylene glycol-(poly-D,L-lactic acid) copolymer (mPEG-PDLLA) and 1 g of docetaxel were weighed, 4 mL of ethanol (EtOH) was added, and the mixture was stirred at 60°C until it was completely dissolved and a transparent solution was obtained. Next, ethanol was removed by vacuum distillation using a rotary vacuum evaporator equipped with a round-bottom flask according to the temperature and time conditions shown in Table 1 below. After that, the temperature was lowered to 28°C, 230 mL of distilled water at room temperature was added, and the reaction was continued until the solution became blue and transparent, forming polymeric micelles within 3 hours.
[0048] When preparing the lyophilized product, 5 g of mannitol as a lyophilizing agent was directly added to the produced polymeric micelles to completely dissolve them, and the mixture was filtered through a filter with a pore size of 200 nm and then lyophilized to produce a powder of a polymeric micelle composition containing docetaxel.
[0049] [Table 1]
[0050] Example 4 and Comparative Examples 2 and 3: Preparation of polymeric micelles containing docetaxel according to micellization conditions The same procedures as in Examples 1 to 3 and Comparative Example 1 were carried out, except that ethanol was removed by reduced pressure distillation according to the conditions shown in Table 2 below. After removing the ethanol, the residual ethanol content was about 0.50 w / v%. Thereafter, the temperature was lowered to the micellization temperature shown in Table 2 below, 230 mL of room temperature distilled water was added, and the mixture was reacted for a predetermined time to form polymer micelles.
[0051] [Table 2]
[0052] Example 5 and Comparative Example 4: Preparation of polymeric micelles containing docetaxel according to storage conditions The same procedure as in Example 1 was repeated, except that the filtered micelles were stored under the conditions shown in Table 3 below. 5 g of mannitol was added as a freeze-drying agent to completely dissolve the micelles. The micelles were then filtered through a filter with a pore size of 200 nm and freeze-dried to produce a powder of a polymeric micelle composition containing docetaxel.
[0053] [Table 3]
[0054] Test example 1: Test to compare deposition times 38 mL of physiological saline was added to 2 g of the polymeric micelles containing docetaxel produced in each of Examples 1 to 3 and 5 and Comparative Examples 1, 3, and 4, and dissolved using an IKA VIBRAX stirrer. The solution was then allowed to stand and observed for docetaxel precipitation every 30 minutes. The results are shown in Table 4 below.
[0055] [Table 4]
[0056] As can be seen from Table 4, when the residual ethanol content was high (Comparative Example 1), the precipitation time was significantly shortened. Also, when the micellization temperature was too high (Comparative Example 3), the drug precipitated during micellization, making production impossible. Furthermore, when the mixture was left at room temperature for a long time after micellization (Comparative Example 4), the precipitation time was significantly shortened.
[0057] Test Example 2: Test to compare related substance contents The test solutions were prepared by filtering the preparations of the docetaxel-containing polymeric micelles produced in each of Examples 1 to 4 and Comparative Example 2 through a 45 μm filter paper, and mixing 1 mL of the filtered solution with 4 mL of HPLC mobile phase solution. The prepared test solutions were subjected to HPLC analysis under the following conditions, and the related substance contents were compared. The related substance contents (%) are shown in Table 5 below.
[0058] HPLC conditions: Column: A stainless steel column with a length of 250 mm and an inner diameter of 4.6 mm, coated with C18 and containing silica gel particles with a particle size of 5 μm and a pore size of 100 Å, or a similar material Mobile phase: Acetonitrile / methanol / water mixture (26 / 32 / 42, v / v / v) Flow rate: 1.5mL / min Detector: UV spectrophotometer (measurement wavelength 232 nm)
[0059] [Table 5]
[0060] As can be seen from Table 5, when the micellization temperature was too high (Comparative Example 2), the content of related substances in the preparation solution increased.
[0061] Test Example 3: Test to compare redissolution times 38 mL of physiological saline was added to 2 g of the polymeric micelles containing docetaxel prepared in each of Examples 1 to 3, Comparative Example 1, and Comparative Example 5, which has a different molecular weight of the polymer, and the time required for the lyophilized solid to completely dissolve (redissolution time) was measured at a stirring speed of 500 rpm using an IKA VIBRAX stirrer. The results are shown in Table 6 below.
[0062] [Table 6]
Claims
1. (1) mixing an active ingredient, an amphiphilic block copolymer having a number average molecular weight of 3,000 to 3,700, and ethanol; (2) removing ethanol from the mixture obtained in step (1) to reduce the ethanol content in the mixture to 0.8 w / v % or less; (3) adding an aqueous medium to the mixture obtained in step (2) to form micelles; and (4) freeze-drying the micelles formed in step (3). Including, The amphiphilic block copolymer comprises a hydrophilic block (A) selected from the group consisting of polyethylene glycol, monomethoxypolyethylene glycol, and combinations thereof; a hydrophobic block (B) selected from the group consisting of polylactide, polyglycolide, poly(lactic acid-glycolide), and combinations thereof; The removal of ethanol is carried out at a temperature greater than 30° C. and less than or equal to 45° C. The formation of micelles is carried out at a temperature below 35° C. A method for producing nanoparticles, characterized in that the micelles formed in step (3) are freeze-dried within 3 hours.
2. The method for producing nanoparticles according to claim 1 , wherein the step of forming micelles includes a process of filtering the formed micelles.
3. The method for producing nanoparticles according to claim 1, wherein the formed micelles are maintained at 0°C to 15°C until freeze-drying is performed.
4. The method for producing nanoparticles according to any one of claims 1 to 3, wherein the active ingredient is a poorly water-soluble drug.
Citation Information
Patent Citations
Amphiphilic block copolymer composition having enhanced micelle stability, and pharmaceutical composition comprising same
EP3556352A1
Method for producing a polymer micelle composition containing a poorly water-soluble drug.
JP2012513984A
Method for producing a water-insoluble drug-containing polymer micelle nanoparticle composition
JP2012513985A
Freeze-dried product of polymer nanoparticles and method for producing the same
JP2018506518A